Cooperative Learning and Case-Based Learning to Improve Spiritual Care Competency in Nursing Students - Aisyah, Popy Siti; Dewi, Inggriane Puspita; Utomo, Shella Febrita Puteri; Hashim, Noraini (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Spiritual care of patients in health services that are not yet optimal needs to be anticipated by nursing education institutions to increase the competence of graduates in spiritual careMethod: Research design used Classroom Action Research (CAR). The study was conducted in three cycles. Each cycle consisted of planning, implementation, observation, and reflection steps. Implementation step used case-based learning. Learning process was performed in the second grade nursing students with lessons about Islamic Spiritual Care and included 19 students and 3 collaborators. Students participated in this study with total sampling method. Successful research was indicated by 85% of students achieving mastery in learning on concept understanding as well as psychomotor aspects. Data collection was performed using documentation method by knowledge test, psychomotor test, observations, and interview. Data were analyzed quantitatively and qualitatively.Results: The results show that all aspects of the spiritual competency nursing student assessed including cognitive, psychomotor, and affective at the end cycle were in good category (100%). The results of the cognitive level test before cooperative learning and case-based learning showed a significant difference with p < 0.001.Conclusion: The implementation of case-based and cooperative learning provides a positive experience for students to more easily understand the application of nursing processes in spiritual care.